Balanceamento de Carga em Clusters por Replicação de Dados Sob Demanda em um SGBDD - Lourenso, Reinaldo; Kofuji, Sergio Takeo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2000: Anais do I Workshop em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad_estendido.2000.19143, 2000)
In the last years, a significant growth of network traffic and processing load has been verified, mainly in database servers. Many factors have been responsible for this growth, such as: growth on demand for information availability, and increase of both size and quantity of stored information, as can be verified in multimedia application. One solution for the problem of processing large volume of information is the utilization of cluster based servers, working together with distributed database systems. This type of solution allows the parallel manipulation of great quantities of information. Although multiprocessing in clusters systems is, in fact, being used more and more due to high performance, low cost and high scalability characteristics, we verified that specific database systems for these architectures present some restrictions in relation to data replication, and load balance. The main objective of this work is the study and implementation of a mechanism that allows a better cluster load balance, in periods of high demand for information, by replicating the most requested data in a Distributed Database Management System (DDBMS). The complete process of copies generation is autonomous, with dynamic distribution of copies for the idle or less loaded node.